Profil pasien endoskopi gastrointestinal di RSUP Prof. Dr. R. D. Kandou periode Januari 2018 - Agustus 2019 - Gunawan, Deborah F.; Waleleng, Bradley J.; Polii, Efata B. I. (e-CliniC, 2019)
Abstract: Along with the development of medical technology, endoscopy is mostly used in determination of the diagnosis and examination of gastrointestinal diseases. This study was aimed to determine the indications of gastrointestinal endoscopy, diagnoses of pre and post endoscopy, sex and age of patients undergoing endoscopy, and the prevalence of endoscopic patients from January 2018 to August 2019 at Prof. Dr. R. D. Kandou Hospital Manado. This was a descriptive and retrospective study using data of Medical Record Installation at Prof. Dr. R. D. Kandou Hospital. The results obtained 495 patients who were endoscopy performed on them. Males were predominant (59.8%) as well as age group of 50-59 years old (22.8%). The most frequent indication of endoscopy was dyspepsia/epigastric pain (68.5%). Moreover, EGD plus colonoscopy was the most common endoscopy performed. GERD (20.45%) had the highest percentage of pre endoscopy diagnosis meanwhile esophagitis Los Angeles Classification Grade A (28.8%) had the highest percentage of post endoscopy diagnosis. In conclusion, gastrointestinal endoscopy was performed more common on males, age group of 50-59 years, with indication of dyspepsia (epigastric pain), and in EGD plus colonoscopy. The most common diagnosis of pre endoscopy was GERD and of post endoscopy was esophagitis Los Angeles Classification Grade A.Keywords: gastrointestinal endoscopyÂ Abstrak: Seiring dengan berkembangnya teknologi dibidang kesehatan, endoskopi yang merupakan salah satu cara penetapan diagnosis dan pemeriksaan gastrointestinal yang banyak digunakan. Penelitian ini bertujuan untuk mengetahui indikasi endoskopi gastrointestinal, diagnosis yang banyak ditemukan sebelum dan sesudah endoskopi, jenis kelamin, usia pasien yang dilakukan endoskopi, dan prevalensi jumlah pasien endoskopi periode Januari 2018 - Agustus 2019 di RSUP Prof. Dr. R. D Kandou. Jenis penelitian ialah deskriptif retrospektif dengan menggunakan data sekunder pasien di Instalasi Rekam Medik RSUP Prof. Dr. R. D. Kandou Manado. Hasil penelitian mendapatkan 495 pasien yang dilakukan pemeriksaan endoskopi selama periode tersebut, dengan 296 pasien (59,8%) yang berjenis kelamin laki-laki. usia terbanyak ialah 50-59 tahun (22,8%), indikasi endoskopi terbanyak ialah dispepsia (nyeri epigastrium) (68,5%), tindakan endoskopi terbanyak dilakukan ialah EGD + kolonoskopi (48,7%). Diagnosis sebelum tindakan terbanyak ialah GERD (20,45%), dan setelah dilakukan endoskopi ialah esofagitis klasifikasi Los Angeles Grade A (28,8%). Simpulan penelitian ini ialah pasien yang melakukan pemeriksaan endoskopi terbanyak berjenis kelamin laki-laki, kelompok usia 50-59 tahun, dengan indikasi dispepsia (nyeri epigastrium). EGD + kolonoskopi merupakan tindakan tersering diterima oleh pasien, diagnosis sebelum tindakan endoskopi ialah GERD, dan setelah dilakukan endoskopi ialah esofagitis klasifikasi Los Angeles Grade A.Kata kunci: endoskopi gastrointestinal